EDUKASI KESEHATAN RAMBUT MELALUI BUKU PEMBELAJARAN GIZI KECANTIKAN RAMBUT PADA MASYARAKAT KECAMATAN MUARA GEMBONG, KABUPATEN BEKASI, JAWA BARAT - Eti Herawati; Elvyra Yulia; Dwi Atmanto; Farah Fatmasari; Munandar Putri Nabila (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2024)
The purpose of education will certainly not be separated from a process called the teaching and learning  process. Currently, teaching and learning activities are not only limited to teachers as educators in  delivering subject matter, but various strategies, technologies and approaches that are tailored to  individual needs and students are required to be active in teaching and learning activities. In order to  improve life and livelihood in the area of Pantai Mekar Muara Gembong village, Bekasi Regency, West  Java. It is necessary to have adequate learning resources and be adjusted to the needs through the provision  of facilities and infrastructure in the form of libraries. One of the books that will be used as a library book  is a book about nutrition for hair health and beauty. The scope of this book is the definition of nutrition,  the content of nutrients needed by hair, and the relationship between nutrition and hair health and beauty. After carrying out counseling in Muara Gembong, there was an increase in knowledge about hair health  nutrition in the trainees (community) with pre-test results in the range of 40-60 amounting to 8 people  (31%), value range 61-80 amounting to 10 people (38%), value range 81-100 amounting to 8 people (31%).  Meanwhile, in the post test, the results in the range of 40-60 amounted to 6 people (23%), the score range  of 61-80 amounted to 12 people (46%), and the score range of 81-100 amounted to 8 people (31%). This  means that there was an increase in knowledge about hair health nutrition for 26 training participants  (community) in the value range of 61-80 as much as (8%). Keywords: hair health, nutritional knowledge, library books Abstrak Tujuan pendidikan tentu nya tidak akan lepas dari suatu proses yang dinamakan dengan proses belajar  mengajar. Saat ini kegiatan belajar mengajar tidak hanya terbatas pada guru sebagai pendidik dalam  penyampaian materi pelajaran, tetapi beragam strategi, teknologi dan pendekatan yang disesuaikan  dengan kebutuhan individual serta peserta didik dituntut untuk aktif dalam kegiatan belajar mengajar.  Dalam rangka meningkatkan kehidupan dan penghidupan di wilayah kelurahan Pantai mekar Muara  Gembong Kabupaten Bekasi, Jawa Barat. Di perlukan sumber belajar yang memadai dan disesuaikan  dengan kebutuhan melalui penyediaan sarana dan prasarana yang berbentuk perpustakan. Salah satu buku yang akan dijadikan buku perpustakaan adalah buku tentang gizi untuk kesehatan dan kecantikan  rambut.Ruang lingkup yang disusun pada buku ini adalah pengertian gizi, kandungan zat gizi yang  dibutuhkan oleh rambut, serta keterkaitan antara gizi dengan kesehatan dan kecantikan rambut. Setelah  melaksanakan penyuluhan di Muara Gembong terjadi peningkatan pengetahuan tentang gizi kesehatan  rambut pada peserta pelatihan (masyarakat) dengan hasil pre test pada rentang 40-60 berjumlah 8 orang  (31%), rentang nilai 61-80 berjumlah 10 orang (38%), rentang nilai 81-100 berjumlah 8 orang (31%). Sedangkan pada post test didapatkan hasil pada rentang 40-60 berjumlah 6 orang (23%), rentang nilai  61-80 berjumlah 12 orang (46%), dan rentang nilai 81-100 berjumlah 8 orang (31%). Artinya, terjadi  peningkatan pengetahuan tentang gizi kesehatan rambut terhadap 26 peserta pelatihan (masyarakat) pada rentang nilai 61-80 sebanyak (8%). Kata Kunci: kesehatan rambut, pengetahuan gizi, buku perpustakaan